Resources: Climate change - International Food Policy Research Institute (International Food Policy Research Institute, 2019)
IFPRI’s mission is to provide research-based policy solutions to sustainably reduce poverty and end hunger and malnutrition. Recent publications and websites share knowledge, tools, and analysis that can contribute to addressing the challenges of climate change.